ANALYSIS OF STUDENTS' ABILITY WITH CONCEPTUAL TEMPO LEARNING STYLE IN SOLVING SPATIAL PROBLEMS: ANALISIS KEMAMPUAN SISWA DENGAN GAYA BELAJAR TEMPO KONSEPTUAL DALAM MEMECAHKAN MASALAH SPASIAL - Satriani, Sri; Kalsum, Umy; Dassa, Awi; Syahri, Andi Alim (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
This study aimed to describe students' spatial abilities in terms of cognitive conceptual tempo style. This type of descriptive qualitative research was conducted at SMP Negeri 26 Makassar with class VIII-2 research subjects. The instruments used in this study were: the MFFT (Matching Familiar Figures Test), spatial ability tests, and interview guidelines. The MFFT test (Matching Familiar Figures Test) was carried out to determine the type of student's cognitive style. Then found 1 subject of impulsive cognitive style and 1 subject of reflective cognitive style. Then the subject was given a spatial ability test to determine the students' spatial abilities after which an interview was conducted. Indicators of spatial ability are: (1) stating the position of the elements of a spatial figure. (2) Constructing and presenting geometric models drawn on a flat plane in a spatial context. (3) imagining the shape or position of a geometric object being viewed from a certain point of view. (4) Investigating the actual size of the visual stimulus of a geometric object. The results showed that students with an impulsive cognitive style had low spatial abilities because they were only able to fulfill 1 spatial ability indicator, namely constructing and presenting geometric models drawn on a flat plane in a spatial context. Meanwhile, students with a cognitive reflective style have high spatial abilities because they are able to fulfill all indicators of spatial abilities.